Analisis Dimensi Profil Pelajar Pancasila melalui Program Kampus Mengajar 7 SD Negeri 2 Langon - Elma Tiara Wulandari; Syailin Nichla Choirin Attalina; Hamidaturrohmah (Universitas Ngudi Waluyo, 2025)
Abstract Independent curriculum learning is oriented towards developing students' character through the implementation of the Pancasila student profile dimensions. In line with this, the government has presented a campus teaching program as a place for collaboration to improve learning innovation. This research took place at SDN 2 Langon with subjects of teachers and students in grades 1, 2, 4, and 5. The purpose of this study was to identify the implementation of the Pancasila student profile dimensions and to analyze the achievement of the Pancasila student profile dimensions through the campus teaching 7 program at SDN 2 Langon. This study uses a qualitative method of field research type with a case study approach through data collection techniques in the form of interviews, observations, and documentation. The data analysis technique is through data reduction, data display, and verification. The findings in this study are that SDN 2 Langon has not held many activity innovations with the P5 work title as a routine agenda. The existence of the campus teaching 7 program has a positive impact on program innovation and implementation of the Pancasila student profile dimensions through priority programs. Technology adaptation program achieves dimensions of independence and critical thinking. Pesantren Ramadhan program achieves dimensions of faith, devotion to God Almighty and noble character. Kartini program realizes the dimensions of global diversity, creativity, and independence. Numeracy literacy festival program achieves the dimensions of mutual cooperation and critical reasoning. P5 program shows the achievements of the dimensions of mutual cooperation, independence, and creativity. Abstrak Pembelajaran kurikulum merdeka berorientasi pada pengembangan karakter peserta didik melalui implementasi dimensi profil pelajar pancasila. Sejalan dengan hal tersebut, pemerintah telah menghadirkan program kampus mengajar sebagai ajang kolaborasi untuk peningkatan inovasi pembelajaran. Penelitian ini berlangsung di SDN 2 Langon dengan subjek guru dan peserta didik kelas 1, 2, 4, dan 5. Tujuan dari penelitian ini adalah untuk mengidentifikasi implementasi dimensi profil pelajar pancasila serta menganalisis ketercapaian dimensi profil pelajar pancasila melalui program kampus mengajar 7 di SDN 2 Langon. Penelitian ini menggunakan metode kualitatif tipe field research dengan pendekatan studi kasus melalui teknik pengumpulan data berupa wawancara, observasi, dan dokumentasi. Adapun teknik analisis data melalui reduksi data, display data, dan verification. Temuan dalam penelitian ini yaitu SDN 2 Langon belum banyak mengadakan inovasi kegiatan dengan gelar karya P5 sebagai agenda rutin. Adanya program kampus mengajar 7 memberikan dampak positif terhadap inovasi program dan implementasi dimensi profil pelajar pancasila melalui program prioritas. Program adaptasi teknologi mencapai dimensi mandiri dan bernalar kritis. Program pesantren Ramadhan mencapai dimensi beriman, bertakwa kepada Tuhan Yang Maha Esa dan berakhlak mulia. Program Kartini tangguh merealisasikan dimensi berkebinekaan global, kreatif, dan mandiri. Program festival literasi numerasi mencapai dimensi gotong royong dan bernalar kritis. Program gelar karya P5 menunjukkan capaian dimensi gotong royong, mandiri, dan kreatif.